Three-metal layered hydroxide room-temperature alcohol-sensitive material as well as preparation method and application thereof
By using tri -metal layer -shaped hydroxide materials, using nickel, zinc, and titanium hydroxide alternately arranged and layered structures to solve the problem of high working temperature of the existing semiconductor alcohol -sensitive material, realized at room temperature at room temperature. High sensitivity and rapid response of alcoholic molecules.
Patent Information
- Application Number
- CN202411469636.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-28
AI Technical Summary
The existing semiconductor alcohol-sensitive materials have high working temperatures, making it difficult to effectively detect alcohol molecules at room temperature, and high temperature activation leads to complex sensor structure, large power consumption, and shortened device life.
The three metal -like hydroxide materials are used alternating the basic skeleton growth unit of nickel, zinc, and titanium hydroxide alternately arranged. Light shooting and oil bath reflux reaction forms a layered structure.
It realizes high sensitivity and rapid response and recovery performance of alcohol molecules (especially ethanol) at room temperature, reducing the activation energy of material sensitivity, and improving the adsorption and sensitive effect of target gas molecules.
Smart Images

Figure CN119375308A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of low-power consumption and high-activity layered gas-sensitive materials, and specifically relates to a tri-metal layered hydroxide room-temperature alcohol-sensitive material and a preparation method and application thereof. Background Art
[0002] Semiconductor gas-sensitive materials are materials that can detect the composition and concentration of gases in the environment. Their electrical properties (such as resistivity) will change significantly with the adsorption and desorption of gases on the surface of the material. They are widely used in gas sensors to detect, leak, alarm and monitor various flammable, explosive or harmful gases in factories, workshops, mines and other places. According to the different conductivity types, semiconductor gas-sensitive materials can be divided into two categories: N-type and P-type. The resistance of N-type gas-sensitive semiconductors will decrease when encountering gas, while the opposite is true for P-type gas-sensitive semiconductors.
[0003] At present, the semiconductor gas-sensitive materials that can detect alcohol molecules mainly include metal oxides, such as tin oxide (SnO2), indium oxide (In2O3), zinc oxide (ZnO), tungsten oxide (WO3) and nickel oxide (NiO), etc. However, the sensitivity and response speed of metal oxides alone in the detection of alcohol molecules need to be improved. In order to improve the detection performance of semiconductor gas-sensitive materials for alcohol gases, researchers have activated composite materials through high temperature. First, they promote the chemical adsorption of the detected gas and oxygen on the surface of the material, second, they activate the surface of the sensitive material through high temperature, and third, they promote the chemical reaction of gas molecules adsorbed on the surface of the material through high temperature to produce strong sensitive signals, thereby improving the overall performance of semiconductor gas-sensitive materials. However, high-temperature activation will lead to problems such as complicated sensor structure, high power consumption, and shortened device life. For the detection of volatile alcohol molecules, the heating device of the sensor may also cause serious problems such as combustion or explosion, which greatly limits the scope of application of such sensors. Therefore, there is an urgent need for a semiconductor alcohol-sensitive material that can detect alcohol molecules at room temperature.
[0004] Layered metal hydroxides are a type of two-dimensional inorganic layered materials, consisting of positively charged metal hydroxide layers, interlayer anions and water molecules. They are usually composed of two-dimensional ultra-thin single-crystalline nanosheets with lateral dimensions ranging from tens of nanometers to several micrometers and thicknesses of tens of nanometers. They have the characteristics of large specific surface area, flexible composition, replaceable anions, and adjustable interlayer spacing. Layered metal salts have attracted much attention in the design and construction of sensitive materials due to their unique growth mode and structural characteristics. The layered structure is conducive to the rapid diffusion of gas molecules and exposes more active sites. In addition, the flexible and variable ion distribution between layers is conducive to the transmission speed of carriers between the entire nanosheet layers, and is expected to be used in the field of high-sensitivity, fast response recovery gas sensors. However, there have been no reports on the use of layered metal hydroxides for the detection of alcohol molecules. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a tri-metal layered hydroxide room temperature alcohol-sensitive material and a preparation method and application thereof, so as to solve the technical problem of high operating temperature of existing semiconductor alcohol-sensitive materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The first aspect of the present invention discloses a tri-metal layered hydroxide room temperature alcohol-sensitive material, which is composed of a plurality of lamellar crystals, each of which is composed of a plurality of layers of basic skeleton growth units; Each layer of basic skeleton growth units is composed of hydroxides of nickel, zinc and titanium. Trivalent nickel ions, titanium ions and divalent zinc ions are arranged alternately and orderly in each layer of basic skeleton growth units; hydroxide ions, ammonium ions and nitrate ions are distributed between each layer of basic skeleton growth units.
[0007] Preferably, carbonate ions are distributed between each layer of basic skeleton growth units.
[0008] Preferably, bicarbonate ions are distributed between each layer of basic skeleton growth units.
[0009] Preferably, the thickness of each lamellar crystal structure is 10-1000 nm.
[0010] The second aspect of the present invention discloses a method for preparing the above-mentioned tri-metal layered hydroxide room temperature alcohol-sensitive material, comprising the following steps: 1) Add solution B dropwise into solution A while stirring to obtain precursor solution C; Solution A is a mixed solution of Ni(NO3)2·6H2O and Zn(NO3)2·6H2O, and solution B is a mixed solution of Ti(OC4H9)4 and 2-methylimidazole. The addition amount of 2-methylimidazole is 5.0 wt% of solution B, and Ni 2+ 、Zn 2+ and Ti 4+ The molar ratio is 1: (0.2~5.0): (0.2~5.0); 2) adding urea to the precursor solution C until the pH value of the solution is 7-14, irradiating with ultraviolet light, reacting under oil bath reflux, separating, washing, and vacuum freeze drying to obtain a room temperature alcohol-sensitive material of a trimetallic layered hydroxide; The amount of urea added is 0.1 wt%~4.5 wt% of the mass percentage concentration of the precursor solution C.
[0011] Preferably, in step 1), the solvent in solution A is deionized water, and the solvent in solution B is isopropanol.
[0012] Preferably, in step 2), a mercury lamp is used for ultraviolet irradiation.
[0013] Further preferably, in step 2), the irradiation power of the ultraviolet light is 50-200 W, and the irradiation time is 0.5-4 h.
[0014] Preferably, in step 2), the conditions for the oil bath reflux reaction are: reflux reaction at 80-95° C. oil bath conditions for 8-24 h.
[0015] Preferably, in step 2), after separation, washing and vacuum freeze-drying are performed.
[0016] More preferably, washing is performed with ethanol and water respectively.
[0017] Preferably, the vacuum freeze-drying conditions are: freeze-drying at a temperature of -80°C to -10°C and a vacuum degree of 20 to 50 Pa for 10 to 40 h.
[0018] The third aspect of the present invention discloses the use of the above-mentioned tri-metal layered hydroxide room temperature alcohol-sensitive material in detecting alcohol molecules.
[0019] Preferably, the alcohol molecule is ethanol.
[0020] The fourth aspect of the present invention discloses a gas sensor comprising the above-mentioned tri-metal layered hydroxide room temperature alcohol sensitive material.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a three-metal layered hydroxide room temperature alcohol-sensitive material, which is composed of a plurality of lamellar crystals, each of which is composed of a plurality of layers of basic skeleton growth units. The basic skeleton growth units composed of hydroxides of nickel, zinc and titanium play a key skeleton support role in the entire material structure. The plurality of lamellar crystal structures are conducive to the rapid diffusion of gas molecules and expose more active sites. The basic skeleton growth units are rich in groups such as hydroxide ions, ammonium ions, and nitrate ions. The flexible and changeable anion distribution between the basic skeleton growth units is conducive to the transmission speed of carriers between the entire nanosheet layer, and has excellent adsorption. Nickel ions, titanium ions and zinc ions, as variable valence metal ions, are alternately and orderly arranged in the basic skeleton growth units of each layer, and can interact with the surrounding oxygen or anions to produce various defects and active sites, which promote and even catalyze the adsorption, response and sensitive reaction of the gas. Therefore, this material is rich in metal ion valence and defects, has a large specific surface area, has high sensitivity and fast response and recovery performance to alcohol molecules (especially ethanol) at room temperature, and is expected to become a highly active gas-sensitive material and be used in the field of high-sensitivity, fast response and recovery alcohol-sensitive sensors.
[0022] The present invention provides a method for preparing the above-mentioned three-metal layered hydroxide room temperature alcohol-sensitive material, 1) based on the catalytic ability of variable valence metals, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Ti(OC4H9)4 are used as reaction raw materials, nickel ions, titanium ions and zinc ions are respectively combined with hydroxide ions to form basic skeleton growth units; Ni(NO3)2·6H2O and Zn(NO3)2·6H2O can also provide adjustable nitrate ions between basic skeleton growth units; 2-methylimidazole is used to control the morphology of the layered structure, thereby controlling the growth (size and lamella distribution) of the basic skeleton growth unit. 2) By adding solution B dropwise to solution A, the hydrolysis of Ti(OC4H9)4 can be slowed down, and the subsequent chemical reaction of generating three metal hydroxides can be effectively controlled. 3) By adding 0.1 wt%~4.5 wt% urea to the mass percentage concentration of the precursor solution C, the pH value of the solution can be adjusted to 7~14, thereby regulating the degree of hydrolysis and reaction of the metal salt, providing the interlayer anions (hydroxyl ions, ammonium ions, etc.) required by the material, and regulating the morphology of the material. 4) The energy required for the reaction is provided by ultraviolet light irradiation, and the reaction is fully carried out by oil bath reflux reaction, so that the precursor solution C of the mixed urea undergoes nucleation, growth, and crystallization to form a Zn / Ni / Ti trimetallic layered hydroxide. This method has low preparation cost, simple preparation, convenient operation, strong controllability, and can effectively improve the adsorption and sensitivity effect of the material to the target gas molecules, reduce the activation energy of the material sensitivity, realize room temperature sensitivity, realize controllable material composition, and regulate the interlayer metal ion valence and defect distribution to obtain a material with a specific particle size and morphology. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of the Zn / Ni / Ti tri-metallic layered hydroxide material prepared in Example 2 of the present invention; Figure 2 This is the XRD pattern of the Zn / Ni / Ti tri-metallic layered hydroxide material prepared in Example 2 of the present invention; Figure 3 This is the response result diagram of Zn / Ni / Ti tri-metallic layered hydroxide material to different alcohols; Figure 4 The concentration-response relationship diagram of the Zn / Ni / Ti tri-metallic layered hydroxide material prepared in Examples 1 to 4 of the present invention to 10 to 50 ppm ethanol; Figure 5 This is a working temperature diagram of the Zn / Ni / Ti tri-metallic layered hydroxide material prepared in Examples 1 to 4 of the present invention for 100 ppm ethanol. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0027] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0028] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0029] The present invention provides a method for preparing a tri-metal layered hydroxide room temperature alcohol-sensitive material, comprising the following steps: 1. Dissolve analytical pure Ni(NO3)2·6H2O and Zn(NO3)2·6H2O in deionized water and stir magnetically until completely dissolved to obtain solution A. Among them, in solution A, Ni 2+ The dosage is 1.0 mmol·L -1 , Ni 2+ With Zn 2+ The molar ratio is =1:(0.2~5.0).
[0030] 2. Dissolve analytically pure Ti(OC4H9)4 in analytically pure isopropanol, add 2-methylimidazole thereto, mix well, and obtain solution B; In solution B, the amount of Ti(OC4H9)4 is 5.0 mmol·L -1The amount of 2-methylimidazole added is 1.0 wt%~10.0 wt% of the mass percentage concentration of the mixed solution B.
[0031] 3. Slowly drop the solution B obtained in step 2 into the solution A obtained in step 1, continue magnetic stirring, then add urea and mix until the pH value of the solution is 7-14 to obtain a precursor solution C; In the precursor solution C, the molar ratio of Ni, Zn and Ti is 1: (0.2~5.0): (0.2~5.0), and the amount of urea added is 0.1 wt%~4.5 wt% of the mass percentage concentration of the precursor solution C.
[0032] 4. Irradiate the precursor solution C with ultraviolet light from a mercury lamp at a power of 50-200 W and an irradiation time of 0.5-4 h. Then reflux the solution in an oil bath at 80-95 °C for 8-24 h, centrifuge it after cooling, wash it with ethanol and water respectively, and finally freeze-dry it at a temperature of -80 °C to -10 °C and a vacuum degree of 20-50 Pa for 10-40 h to obtain a room temperature alcohol-sensitive material of a trimetallic layered hydroxide.
[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0034] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercial products, and their specifications are conventional specifications in the art.
[0035] Example 1 1. Dissolve analytical pure Ni(NO3)2·6H2O and Zn(NO3)2·6H2O in deionized water. 2+ The dosage is 1.0mmol·L -1 , Zn 2+ The dosage is 0.2 mmol·L -1 , stir magnetically until completely dissolved to obtain solution A; 2. Set the molar concentration to 5.0 mmol·L -1 Analytical pure Ti(OC4H9)4 was dissolved in analytical pure isopropanol, and 2-methylimidazole with a mass percentage concentration of 5.0 wt% was added and mixed uniformly to obtain solution B; 3. Under continuous magnetic stirring, solution B was slowly added dropwise to solution A to make the molar ratio of Ni / Zn / Ti in the mixed solution be 1:0.2:1, and then urea reagent with a mass percentage concentration of 2.5 wt% was added to the mixed solution until the pH value of the solution was 7, thereby obtaining a precursor solution C; 4. The precursor solution C was placed in a round-bottom flask, irradiated with ultraviolet light from a 100 W mercury lamp for 4 h, then refluxed in an oil bath at 80 °C for 10 h, cooled, centrifuged, washed with ethanol and water respectively, and finally freeze-dried at -50 °C and a vacuum degree of 20 Pa for 40 h to obtain a Zn / Ni / Ti trimetallic layered hydroxide material.
[0036] Example 2 1. Dissolve analytical pure Ni(NO3)2·6H2O and Zn(NO3)2·6H2O in deionized water. 2+ and Zn 2+ The dosage was 1.0 mmol·L -1 , stir magnetically until completely dissolved to obtain solution A; 2. Set the molar concentration to 5.0 mmol·L -1 Analytical pure Ti(OC4H9)4 was dissolved in analytical pure isopropanol, and 2-methylimidazole with a mass percentage concentration of 3.0 wt% was added and mixed uniformly to obtain solution B; 3. Under continuous magnetic stirring, solution B was slowly added dropwise to solution A to make the molar ratio of Ni / Zn / Ti in the mixed solution be 1:1:2, and then urea with a mass percentage concentration of 1.5 wt% was added to the mixed solution until the pH value of the solution was 10, thereby obtaining a precursor solution C; 4. The precursor solution C was placed in a round-bottom flask, irradiated with ultraviolet light from a 50 W mercury lamp for 4 h, then refluxed in an oil bath at 80 °C for 24 h, cooled, centrifuged, washed with ethanol and water respectively, and finally freeze-dried at -40 °C and a vacuum degree of 30 Pa for 24 h to obtain a Zn / Ni / Ti trimetallic layered hydroxide material.
[0037] The results of SEM (scanning electron microscope) and X-ray diffractometer (XRD) were as follows: Figure 1 and Figure 2As shown, it can be seen that the prepared Zn / Ni / Ti trimetallic layered hydroxide material contains several lamellar crystal structures with a thickness of 10~1000 nm, indicating that the method can obtain the target material, and each lamellar crystal structure is composed of several layers of basic skeleton growth units, each layer of basic skeleton growth unit is composed of nickel, zinc and titanium hydroxides, and trivalent nickel ions, titanium ions and divalent zinc ions are alternately arranged in order in each layer of basic skeleton growth unit; hydroxide ions, ammonium ions, nitrate ions, carbonate ions and bicarbonate ions are distributed between each layer of basic skeleton growth units, which further indicates that the material has good sensitivity.
[0038] Example 3 1. Dissolve analytical pure Ni(NO3)2·6H2O and Zn(NO3)2·6H2O in deionized water. 2+ The dosage is 1.0mmol·L -1 , Zn 2+ The dosage is 2.0 mmol·L -1 , stir magnetically until completely dissolved to obtain solution A; 2. Set the molar concentration to 5.0 mmol·L -1 Analytical pure Ti(OC4H9)4 was dissolved in analytical pure isopropanol, and 2-methylimidazole with a mass percentage concentration of 7.0 wt% was added and mixed uniformly to obtain solution B; 3. Under continuous magnetic stirring, solution B was slowly added dropwise to solution A to make the molar ratio of Ni / Zn / Ti in the mixed solution be 1:2:3, and then urea with a mass percentage concentration of 2.5 wt% was added to the mixed solution until the pH value of the solution reached 8, thereby obtaining a precursor solution C; 4. The precursor solution C was placed in a round-bottom flask and irradiated with ultraviolet light from a 100 W mercury lamp for 3 h, then refluxed in an oil bath at 85 °C for 18 h, cooled, centrifuged, washed with ethanol and water respectively, and finally freeze-dried at -80 °C and a vacuum degree of 50 Pa for 10 h to obtain a Zn / Ni / Ti trimetallic layered hydroxide material.
[0039] Example 4 1. Dissolve analytical pure Ni(NO3)2·6H2O and Zn(NO3)2·6H2O in deionized water. 2+ The dosage is 1.0mmol·L -1 , Zn 2+ The dosage is 1.0 mmol·L -1 , stir magnetically until completely dissolved to obtain solution A; 2. Set the molar concentration to 5.0 mmol·L -1 Analytical pure Ti(OC4H9)4 was dissolved in analytical pure isopropanol, and 2-methylimidazole with a mass percentage concentration of 10.0 wt% was added and mixed uniformly to obtain solution B; 3. Under continuous magnetic stirring, solution B was slowly added dropwise to solution A to make the molar ratio of Ni / Zn / Ti in the mixed solution be 1:1:0.5, and then urea with a mass percentage concentration of 4.5 wt% was added to the mixed solution until the pH value of the solution reached 9, thereby obtaining a precursor solution C; 4. The precursor solution C was placed in a round-bottom flask and irradiated with ultraviolet light from a 200 W mercury lamp for 0.5 h, then refluxed in an oil bath at 95 °C for 8 h, cooled, centrifuged, washed with ethanol and water respectively, and finally freeze-dried at -10 °C and a vacuum degree of 50 Pa for 25 h to obtain a Zn / Ni / Ti trimetallic layered hydroxide material.
[0040] Example 5 1. Dissolve analytical pure Ni(NO3)2·6H2O and Zn(NO3)2·6H2O in deionized water. 2+ The dosage is 1.0mmol·L -1 , Zn 2+ The dosage is 4.0 mmol·L -1 , stir magnetically until completely dissolved to obtain solution A; 2. Set the molar concentration to 5.0 mmol·L -1 Analytical pure Ti(OC4H9)4 was dissolved in analytical pure isopropanol, and 2-methylimidazole with a mass percentage concentration of 1.0 wt% was added and mixed uniformly to obtain solution B; 3. Under continuous magnetic stirring, solution B was slowly added dropwise to solution A to make the molar ratio of Ni / Zn / Ti in the mixed solution be 1:4:2, and then urea with a mass percentage concentration of 0.1 wt% was added to the mixed solution until the pH value of the solution was 10, thereby obtaining a precursor solution C; 4. The precursor solution C was placed in a round-bottom flask and irradiated with ultraviolet light from a 100 W mercury lamp for 2 h, then refluxed in an oil bath at 85 °C for 14 h, cooled, centrifuged, washed with ethanol and water respectively, and finally freeze-dried at -30 °C and a vacuum degree of 30 Pa for 20 h to obtain a Zn / Ni / Ti trimetallic layered hydroxide material.
[0041] Example 6 1. Dissolve analytical pure Ni(NO3)2·6H2O and Zn(NO3)2·6H2O in deionized water. 2+The dosage is 1.0mmol·L -1 , Zn 2+ The dosage is 5.0 mmol·L -1 , stir magnetically until completely dissolved to obtain solution A; 2. Set the molar concentration to 5.0 mmol·L -1 Analytical pure Ti(OC4H9)4 was dissolved in analytical pure isopropanol, and 2.0 wt% of 2-methylimidazole was added and mixed well to obtain solution B; 3. Under continuous magnetic stirring, solution B was slowly added dropwise to solution A to make the molar ratio of Ni / Zn / Ti in the mixed solution be 1:5:0.2, and then urea with a mass percentage concentration of 0.25 wt% was added to the mixed solution until the pH value of the solution was 11, thereby obtaining a precursor solution C; 4. The precursor solution C was placed in a round-bottom flask and irradiated with ultraviolet light from a 60 W mercury lamp for 3 h, then refluxed in an oil bath at 80 °C for 20 h, cooled, centrifuged, washed with ethanol and water respectively, and finally freeze-dried at -50 °C and a vacuum degree of 40 Pa for 20 h to obtain a Zn / Ni / Ti trimetallic layered hydroxide material.
[0042] Example 7 1. Dissolve analytical pure Ni(NO3)2·6H2O and Zn(NO3)2·6H2O in deionized water. 2+ The dosage is 1.0mmol·L -1 , Zn 2+ The dosage is 4.0 mmol·L -1 , stir magnetically until completely dissolved to obtain solution A; 2. Set the molar concentration to 5.0 mmol·L -1 Analytical pure Ti(OC4H9)4 was dissolved in analytical pure isopropanol, and then 8.0 wt% of 2-methylimidazole was added and mixed well to obtain solution B; 3. Under continuous magnetic stirring, solution B was slowly added dropwise to solution A to make the molar ratio of Ni / Zn / Ti in the mixed solution be 1:4:5, and then urea with a mass percentage concentration of 0.25 wt% was added to the mixed solution until the pH value of the solution was 12, thereby obtaining a precursor solution C; 4. The precursor solution C was placed in a round-bottom flask, irradiated with ultraviolet light from a mercury lamp with a power of 80 W for 2 h, then refluxed in an oil bath at 80 °C for 22 h, cooled, centrifuged, washed with ethanol and water respectively, and finally freeze-dried at -50 °C and a vacuum degree of 40 Pa for 20 h to obtain a Zn / Ni / Ti trimetallic layered hydroxide material.
[0043] The performance of the Zn / Ni / Ti tri-metallic layered hydroxide materials prepared in Examples 1 to 4 was tested.
[0044] 1. Response experiment of Zn / Ni / Ti trimetallic layered hydroxide materials to different alcohols The Zn / Ni / Ti tri-metallic layered hydroxide material prepared in the above Example 2 was made into a slurry and coated on a ceramic tube. Then, the ceramic tube coated with the Zn / Ni / Ti tri-metallic layered hydroxide material was welded to a WS-30A gas sensitive detector. The resistance values (Ra and Rg) of the Zn / Ni / Ti tri-metallic layered hydroxide material in air and different alcohol molecules (20 ppm methanol, n-pentanol, isopropanol and ethanol) were measured in a closed space, and the response value S=Rg / Ra was calculated.
[0045] The experimental results are as follows Figure 3 As shown, it can be seen that the Zn / Ni / Ti tri-metallic layered hydroxide material has sensitivity and response speed to different alcohol molecules, especially for ethanol, it has a more unique selectivity advantage.
[0046] 2. Response experiment of Zn / Ni / Ti trimetallic layered hydroxide materials to different concentrations of ethanol The Zn / Ni / Ti trimetallic layered hydroxide materials prepared in Examples 1 to 4 were respectively made into slurries and coated on ceramic tubes. Then, the ceramic tubes coated with the Zn / Ni / Ti trimetallic layered hydroxide materials were welded on a WS-30A gas sensitive detector. The resistance values (Ra and Rg) of different Zn / Ni / Ti trimetallic layered hydroxide materials in air and 10 to 50 ppm ethanol atmosphere were measured in a closed space, and the response values S = Rg / Ra of different concentrations of Zn / Ni / Ti trimetallic layered hydroxide materials to different concentrations of ethanol were calculated.
[0047] The experimental results are as follows Figure 4 As shown, it can be seen that the concentration-response of the material conforms to the linear growth law, among which the material prepared in Example 2 has the best sensitivity.
[0048] 3. Response experiment of Zn / Ni / Ti trimetallic layered hydroxide material to ethanol under different temperature conditions The Zn / Ni / Ti trimetallic layered hydroxide materials prepared in Examples 1 to 4 were respectively made into slurries and coated on ceramic tubes. Then, the ceramic tubes coated with the Zn / Ni / Ti trimetallic layered hydroxide materials were welded on a WS-30A gas sensitive detector. The resistance values (Ra and Rg) of different Zn / Ni / Ti trimetallic layered hydroxide materials in air and 100 ppm ethanol atmosphere were measured in a closed space at different temperatures (20, 30, 40, 50, 60, 70, 80, 90°C), and the response values S=Rg / Ra of different concentrations of Zn / Ni / Ti trimetallic layered hydroxide materials to ethanol at different temperatures were calculated.
[0049] The experimental results are as follows Figure 5 As shown, it can be seen that the optimal working temperature of the Zn / Ni / Ti tri-metallic layered hydroxide material is 30°C, indicating that the Zn / Ni / Ti tri-metallic layered hydroxide material prepared by this method can achieve the goal of room temperature sensitivity.
[0050] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A three-metal layered hydroxide room temperature alcohol-sensitive material, characterized in that: It is composed of several lamellar crystals, each of which is composed of several layers of basic skeleton growth units; Each layer of basic skeleton growth units is composed of hydroxides of nickel, zinc and titanium. Trivalent nickel ions, titanium ions and divalent zinc ions are arranged alternately and orderly in each layer of basic skeleton growth units; hydroxide ions, ammonium ions and nitrate ions are distributed between each layer of basic skeleton growth units.
2. A three-metal layered hydroxide room temperature alcohol-sensitive material according to claim 1, characterized in that: Carbonate ions are also distributed between each layer of basic skeleton growth units.
3. A three-metal layered hydroxide room temperature alcohol-sensitive material according to claim 1, characterized in that: Bicarbonate ions are also distributed between each layer of basic skeleton growth units.
4. A three-metal layered hydroxide room temperature alcohol-sensitive material according to any one of claims 1 to 3, characterized in that: The thickness of the lamellar crystals is 10~1000 nm.
5. A method for preparing a three-metal layered hydroxide room temperature alcohol-sensitive material according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Add solution B dropwise into solution A while stirring to obtain precursor solution C; Solution A is a mixed solution of Ni(NO3)2·6H2O and Zn(NO3)2·6H2O, and solution B is a mixed solution of Ti(OC4H9)4 and 2-methylimidazole. The addition amount of 2-methylimidazole is 5.0 wt% of solution B, and Ni 2+ 、Zn 2+ and Ti 4+ The molar ratio is 1: (0.2~5.0): (0.2~5.0); 2) Add urea to the precursor solution C, irradiate with ultraviolet light, reflux in an oil bath for reaction, and separate to obtain a room temperature alcohol-sensitive material of a trimetallic layered hydroxide; The amount of urea added is 0.1 wt%~4.5 wt% of the mass percentage concentration of the precursor solution C.
6. The method for preparing a tri-metal layered hydroxide room temperature alcohol-sensitive material according to claim 5, characterized in that: In step 1), the solvent in solution A is deionized water, and the solvent in solution B is isopropanol.
7. The method for preparing a tri-metal layered hydroxide room temperature alcohol-sensitive material according to claim 5, characterized in that: In step 2), the conditions for the oil bath reflux reaction are: reflux reaction at 80-95° C. in an oil bath for 8-24 h.
8. Use of a room temperature alcohol-sensitive trimetallic layered hydroxide material according to any one of claims 1 to 4 in detecting alcohol molecules.
9. The use according to claim 8, characterized in that: The alcohol molecule is ethanol.
10. A gas sensor, characterized in that: The invention comprises the room temperature alcohol-sensitive material of the tri-metal layered hydroxide according to any one of claims 1 to 4.